Cationic Palladium Catalyzed Nonalternating Copolymerization of Ethylene with Carbon Monoxide: Microstructure Analysis and Computational Study†. Issue 4 (28th December 2022) - Li, Shi‐Huan; Pan, Ru‐Chao; Ren, Bai‐Hao; Yang, Jian‐Wei; Kang, Xiaohui; Liu, Ye
Comprehensive Summary: The introduction of carbonyl group with a high density in polyethylene backbone corresponds to polyketone materials, which features excellent mechanical strength, crystallinity, photodegradability, hydrophilicity, surface and barrier properties. Due to the extremely high binding affinity of carbon monoxide (CO) and kinetic preference for its subsequent insertion, the formation of nonalternating structure with extra ethylene insertion is exceptionally challenging, however, this nonalternating strategy is of significant importance for polymer modification in term of processing and solubility. Here, we have communicated our study on cationic palladium coordinated diphosphazane monoxide (PNPO) for the nonalternating copolymerization of ethylene with CO, the systematical investigation on the amine and phosphine oxide moieties in PNPO platform in term of electronic and steric modulation has been performed. It is discovered that the installation of aliphatic structure on amine moiety favors the improvement of catalyst activity and longevity, while the amino groups on phosphine oxide moiety promotes the nonalternating copolymerization. In particular, we have computationally investigated herein the aspects of the nonalternating degree by comparing with PNPO platform and 1, 3‐bis(diphenylphosphanyl)propane ligands based palladium catalysts. These mechanistic studies can help to understand the catalyst structure and polyketone property relationships and shed light on future design of high‐performance copolymerization catalysts. Abstract :